Epidemiology and the Delivery of Health Care Services Methods and Applications - Oleske, Denise M. (Springer US, 2001)
In the previous edition of this book, the predominant theme was applying epidemiology to assist managers in dealing with an environment in which the structure of health care financing was rapidly changing to managed care and in which there was increasing competition among health care providers. While these phenomena continue to exist, new challenges have emerged, and in particular the explosion of information technology has given way to a global society and decision making that is increasingly shared with consumers because of their access to the same sets of data. Thus, the questions with which health care managers are confronted on a daily basis are now exceedingly more complex: (1) How can a population be defined considering that both exposures and diseases originating in one corner of the globe can rapidly become a threat to any nationỚ"s security? (2) Where do influences on a population begin and end? (3) How can we protect and promote health in that population or any population if privacy is preeminent? This edition brings in this editorỚ"s view of the increasing need for health care managers, be they in private or public settings, to use epidemiological concepts and methods. The ch- lenges posed by health care delivery in the 21st century are immense, ranging from redefining life and health given the advances in genetic technology, global environmental changes, and multinational simultaneous increases in poverty and longevity, to economic decisions rega- ing technology and service levels that fewer and fewer can afford.